2000
DOI: 10.1086/302922
|View full text |Cite
|
Sign up to set email alerts
|

Founder Mutations in the BRCA1 Gene in Polish Families with Breast-Ovarian Cancer

Abstract: We have undertaken a hospital-based study, to identify possible BRCA1 and BRCA2 founder mutations in the Polish population. The study group consisted of 66 Polish families with cancer who have at least three related females affected with breast or ovarian cancer and who had cancer diagnosed, in at least one of the three affected females, at age <50 years. A total of 26 families had both breast and ovarian cancers, 4 families had ovarian cancers only, and 36 families had breast cancers only. Genomic DNA was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
190
4
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(212 citation statements)
references
References 24 publications
15
190
4
2
Order By: Relevance
“…This study extends our previous work on familial breast-ovarian cancer in Poland. 11,24 In a previous study, 24 we found one of the 3 common founder BRCA1 mutations in 49 of 364 (13.5%) women with unselected ovarian cancer. Given that the 3 founder mutations are responsible for 91% of BRCA1 mutations, we now estimate the prevalence of all BRCA1 mutations among ovarian cancer cases in Poland to be 14.8%.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This study extends our previous work on familial breast-ovarian cancer in Poland. 11,24 In a previous study, 24 we found one of the 3 common founder BRCA1 mutations in 49 of 364 (13.5%) women with unselected ovarian cancer. Given that the 3 founder mutations are responsible for 91% of BRCA1 mutations, we now estimate the prevalence of all BRCA1 mutations among ovarian cancer cases in Poland to be 14.8%.…”
Section: Discussionmentioning
confidence: 73%
“…Smaller studies, cited in Table V, reported 50 mutations (39%) in 127 families with at least 3 affected relatives. [11][12][13][14][15][16][17]25,30 The proportion of families with BRCA1 mutations in our series is much higher (64%). It is possible that the average family size in the present study is larger than that in the smaller series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Ancestry-informed testing of a few common BRCA1/2 mutations has been proposed as a cost-effective approach in a number of populations including Ashkenazi Jews. [18][19][20][21][22][23][24][25] Diagnosing BRCA mutations triggers preventive measures in relatives, which contributes to the value of such screening approaches. 21 The identification of a prevalent founder mutation in a very specific part of the Tyrol may facilitate a long-term study to examine the true sensitivity, usefulness, and cost-effectiveness of routine testing of breast or ovarian cancer patients without any selection based on established HBOC criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Founder mutations in BRCA1 gene have been recently described in Eastern Baltic Sea region, with variable distribution in Baltic (Latvian [1] and Lithuanian [2]) and Slavic (Polish [3], Belorussian [4], Russian [5]) populations, accounting for 80-90% of all mutations. However, data about its incidence in Lithuania are inconclusive and based on one study where only three mutations were tested in BRCA1 gene [2].…”
Section: Introductionmentioning
confidence: 99%